The classics of interest group behavior - Alexander, Robert M., 1972- (Thomson/Wadsworth, 2006)
"An edited collection of articles on interest group behavior, this reader includes a combination of classic and contemporary readings with topics including group formation and mobilization, group behavior, and influence. An introductory chapter to the book includes a general overview and discussion of research in the area of Interest Groups and in each chapter there is a brief overview to each section, a summary chapter that discusses the future of research as well as suggestions for further reading, including internet resources."--Publisher.